Unsettling settler societies articulations of gender, race, ethnicity and class - Stasiulis, Daiva K.; Yuval-Davis, Nira.; Sage eBooks (London : SAGE, 1995)
This book considers the relation between indigenous and settler/immigrant populations, focusing in particular on women's conditions and politics. It examines how the process of development of settler societies and the positions of indigenous and migrant peoples within them, reflects the place of these societies (New Zealand, Australia, Canada, the United States, Mexico, Peru, South Africa, Zimbabwe, Algeria and Israel) within a global economy.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Colonies -- History; Europe -- Colonies -- History; Sex role -- History; Ethnic relations -- History; Electronic books